Do Homeowners Benefit the Neighborhood? Evidence from Semiparametric Hedonic Regressions - Tuukka Saarimaa; Mika Kortelainen (European Regional Science Association (ERSA), 2012)
Homeownership is heavily subsidized in many countries mainly through the tax code. The adverse effects of lenient tax treatment of owner-occupied housing on economic efficiency and growth are well documented in the economics literature. The main argument in favor of subsidizing owner-occupied housing is that it creates positive externalities or social benefits that offset these adverse effects. This paper tests whether homeowners create positive externalities to their immediate neighborhood that capitalize into house prices. Using semiparametric hedonic regressions with instrumental variables we find no evidence of positive externalities from neighborhood homeownership rate. This result is robust to relaxing the identification assumptions of our instrument using the set identification method proposed by Nevo and Rosen (2012, Review of Economics and Statistics, forthcoming). Our results suggest that the adverse efficiency effects of lenient tax treatment of owner-occupied housing are not offset by positive externalities.
Keywords: D62; R21; R28; 330; Homeownership; neighborhood effects; partial linear model; kernel regression; set identification